Knowledge and perception about the ongoing COVID-19 pandemic among patients attending a rural primary health care facility in Delhi - Arora, Ekta; Budh, Nidhi; Katre, Rohit; Banerjee, Bratati (International Journal Of Community Medicine And Public Health, 2021)
Another decade is suffering from the wrath of another coronavirus. Currently, this pandemic has spread to almost all countries of the world taking lives of millions of people globally. This study has uncovered the perceived facts about COVID-19 by general population as well as the effect of IEC in modulating their perception and presenting right amount of information in a scientific manner. A cross-sectional, descriptive study was carried out at rural health training center, Barwala on patients attending out-patient department at RHTC, for a duration of 2 months. Pre-tested questionnaire for assessing public perception and awareness were used to collect data. Appropriate statistical tests were applied to find out association between different variables. Majority of study subjects (98.5%) were aware about the ongoing pandemic of COVID-19. Out of the total study subjects, 90% of them had correct knowledge about various preventive strategies undertaken to break the chain of transmission. However, only about half of the study subjects (53.1%) had correct knowledge regarding various modes of transmission of novel coronavirus. Motivating the people to report any possible infection and to follow the preventive strategies being recommended by experts on timely basis is an important aspect to curb the ongoing menace of COVID-19.